Residential trajectories in the Lisbon Metropolitan Area: social profiles, mobility and tenure status - Pinto, T. C. (2017)
The article is the result of the research project ‘Residential Trajectories and Metropolization: Continuities and Changes in the Lisbon Metropolitan Area’ and analyses the residential trajectories of families in Lisbon. Following some international studies, our overriding objective is to examine the relationship between housing dynamics and family and professional contexts related to moving house. We observe three generations (born between 1945–1954, 1955–1964 and 1965–1975) in central Lisbon and the northern and southern metropolitan areas. More specifically, this article aims to explore three fundamental dimensions: (1) the intensity of the residential mobility of households in Lisbon and the profiles associated with more and less mobility; (2) the typology of trajectories in relation to tenure status as well as an analysis of the profiles associated with each type of trajectory; and 3) the different reasons for moving house during the residential trajectory. The research outcomes on housing trajectories seem to indicate limited residential mobility due to the historical dynamics of the housing market in Portugal and the social and cultural options of families that tend to prefer home ownership. Moreover, the research indicates that family and social class are pertinent variables when analysing housing movements in the Lisbon Metropolitan Area.